2023
DOI: 10.2147/ijgm.s423016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Clinical Effect of Percutaneous Kyphoplasty for Osteoporosis Vertebral Compression Fracture Patient with or Without Sarcopenia: A Retrospective Cohort Study

Abstract: Background: Sarcopenia and osteoporosis vertebral compression fractures (OVCF) are common diseases that increase with age. This study aimed to investigate the effects of sarcopenia on OVCF patients after percutaneous kyphoplasty (PKP). Methods: Data of 101 patients who were treated with single-level PKP between January 2021 and March 2022 at Ningbo No.6 Hospital were enrolled. Forty-five OVCF patients with sarcopenia who met our inclusion criteria were included in the Sarcopenia-PKP group (SPKP group), and 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Sho [ 26 ] and colleagues have illustrated how sarcopenia impacts LBP and daily life for osteoporosis patients. Additionally, Yu [ 27 ] and team have demonstrated that sarcopenia diminishes the clinical efficacy of PKP. Hence, it is reasonable to hypothesize that sarcopenia may influence the alleviation of LBP following PKP in patients with OVCFs.…”
Section: Discussionmentioning
confidence: 99%
“…Sho [ 26 ] and colleagues have illustrated how sarcopenia impacts LBP and daily life for osteoporosis patients. Additionally, Yu [ 27 ] and team have demonstrated that sarcopenia diminishes the clinical efficacy of PKP. Hence, it is reasonable to hypothesize that sarcopenia may influence the alleviation of LBP following PKP in patients with OVCFs.…”
Section: Discussionmentioning
confidence: 99%
“…The debate continues over sarcopenia's influence on the postoperative prognosis in OVCF patients. Research encompassing 101 subjects indicates that muscle atrophy may compromise the clinical efficacy of PVP interventions 30 . Nevertheless, this assertion is not universally supported.…”
Section: Discussionmentioning
confidence: 99%